Asean and East Asian international relations regional delusion - Jones, David Martin; Smith, M. L. R. (Michael Lawrence Rowan) 1963- (Edward Elgar, 2006)
Academic and accepted orthodoxy maintains that Southeast Asia, and Asia generally, is evolving into a distinctive East Asian regional order. This book questions this claim and reveals instead uncertainty and incoherence at the heart of ASEAN, the region's foremost institution. The authors provide a systematic critique of ASEAN's evolution and institutional development, as well as a unified understanding of the international relations and political economy of ASEAN and the Asia-Pacific. It is the first study to provide a sceptical analysis of international relations orthodoxies regarding regionalization and institutionalism, and is based on wide-ranging and rigorous research.